Corking Nitrogen-Doped Carbon Nanotube Cups with Gold Nanoparticles for Biodegradable Drug Delivery Applications - Burkert, Seth C. (Curr Protoc Chem Biol, 2015)
Carbon nanomaterials have been proposed as effective drug delivery devices; however their perceived biopersistence and toxicological profile may hinder their applications in medical therapeutics. Nitrogen doping of carbon nanotubes results in a unique “stacked-cup” structure, with cups held together through van der Waals forces. Disrupting these weak interactions yields individual and short-stacked nanocups which can be subsequently corked with gold nanoparticles resulting in sealed containers for delivery of cargo. Peroxidase-catalyzed reactions can effectively uncork these containers, followed by complete degradation of the graphitic capsule, resulting in effective release of therapeutic cargo while minimizing harmful side effects. The protocols reported herein describe the synthesis of stacked nitrogen-doped carbon nanotube cups followed by effective separation into individual cups and gold nanoparticle cork formation resulting in loaded and sealed containers.